Behavioural nudges for promoting supply and demand for quality seed of improved sweetpotato varieties - Okello, J.J.; Rajendran, S.; Ogero, K. (2025)
This research brief evaluates the use of behavioral “nudges” to enhance demand and adoption of certified sweetpotato seed among smallholder farmers in Uganda. A randomized controlled trial was implemented in Amuria District with 1,200 farmers across 120 villages, divided into treatment and control groups. The intervention tested low-cost psychological and social nudges—nostalgia, loss aversion, and SMS reminders—alongside supply-side enablers such as verified seed vendors and equal physical access points. Results showed that nudges increased certified vine purchases by 6.5%, with farmers high in nostalgic sensitivity showing a 15% higher uptake. The effects persisted across three planting seasons but diminished with repetition, emphasizing context specificity and temporal limits. The study concludes that behavioral interventions, when combined with functional seed supply systems, can cost-effectively accelerate adoption and strengthen national seed markets for vegetatively propagated crops.